A Novel Mechanism of the c-Myc/NEAT1 Axis Mediating Colorectal Cancer Cell Response to Photodynamic Therapy Treatment - Liu, Kuijie; Lei, Sanlin; Kuang, Yong; Jin, Qianqian; Long, Dongju; Liu, Chao; Jiang, Yuhong; Zhao, Hua; Yao, Hongliang (Frontiers in Oncology, 2021)
Photodynamic therapy (PDT) is a potential therapy for colorectal cancer (CRC). The p53 signaling and the miR-124/iASPP axis play an important role in PDT resistance of CRC cells. PDT treatment downregulated NEAT1 expression in p53wt HCT116 and RKO cells. In these two cell lines, NEAT1 silencing enhanced the suppressive effects of PDT on cell viability and apoptosis. Within subcutaneously implanted tumor model, NEAT1 silencing enhanced PDT-induced suppression on tumor growth. In p53-deleted HCT116 cells, PDT only moderately affected cell proliferation but caused downregulation of NEAT1. NEAT1 directly targeted miR-124, acting as a ceRNA, competing with iASPP for miR-124 binding, and counteracting miR-124-mediated repression on iASPP under PDT treatment. NEAT1 silencing enhanced, whereas miR-124 inhibition attenuated PDT effects on CRC cells; miR-124 inhibition significantly reversed the roles of NEAT1 silencing in PDT-treated CRC cells. miR-124 negatively correlated with NEAT1 and iASPP, respectively, whereas NEAT1 and iASPP positively correlated with each other. PDT downregulated c-Myc in CRC cells and c-Myc activated the transcription of NEAT1 via targeting its promoter region. Within p53mut SW480 cells, PDT failed to alter cell viability and apoptosis but still downregulated c-Myc, NEAT1, and iASPP and upregulated miR-124. In p53 mutant high-abundant CRC tissues, c-Myc and NEAT1 were upregulated and miR-124 was downregulated. In c-Myc high-abundant CRC tissues, NEAT1 and iASPP were upregulated and miR-124 was downregulated. Altogether, we demonstrated the critical role of the c-Myc/NEAT1 axis in mediating CRC response to PDT treatment via the miR-124/iASPP/p53 feedback loop.